2022
DOI: 10.1186/s12891-022-05579-0
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a circular RNA-based competing endogenous RNA network to screen biomarkers related to intervertebral disc degeneration

Abstract: Background Intervertebral disc degeneration (IDD) is a leading cause of disability with limited treatment strategies. A better understanding of the mechanism of IDD might enable less invasive and more targeted treatments. This study aimed to identify the circular RNA (circRNA)–microRNA (miRNA)–messenger RNA (mRNA) competing endogenous RNA (ceRNA) regulatory mechanisms in IDD. Methods  The GSE67567 microarray dataset was downloaded from the Gene Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…However, unlike this study, the mRNA data was not integrated. Similarly, other studies constructed ceRNA research networks using GEO databases, but the circRNA, mRNA, and miRNA databases chosen in this study differed from those utilized in the aforementioned studies 13 , 35 , 36 . Future research could summarize these studies to obtain more precise potential regulatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike this study, the mRNA data was not integrated. Similarly, other studies constructed ceRNA research networks using GEO databases, but the circRNA, mRNA, and miRNA databases chosen in this study differed from those utilized in the aforementioned studies 13 , 35 , 36 . Future research could summarize these studies to obtain more precise potential regulatory sites.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that endogenous non-coding RNAs (ncRNAs), including circular RNAs (circRNAs) and microRNAs (miRNAs), participate in numerous biological and pathological processes. [12][13][14][15][16] Signi cantly, circRNAs have a complete circular structure with the characteristics of stabilization and biological functional diversity. Several studies have indicated that circRNAs act as sponges for miRNAs and speci cally bind to them.…”
Section: Introductionmentioning
confidence: 99%